Psychological factors of suicidal risk among adolescents with speech disorders - Olga L. Panchenko, Flera G. Mukhametzyanova,; Alexey A. Sharov, Tanzilya F. Rudsinskaya, (Opción, 2019)
The purpose of this article is to present the main conclusions on the results of the ascertaining experiment and to identify the relationship between the empathy level, the severity of character accentuations, and the tendency to suicidal risk in adolescents with speech disorders. We used a comprehensive methodology during the study. Results of the study showed that there were indicators of the empathy level and suicidal risk propensity in certain groups of subjects. In conclusion, the relationship between a high empathy level and suicidal risk propensity, as well as between cyclical and demonstrative types of accentuations, has been empirically proven.